Strengthening Vocational Education: Analyzing the Match between TVL Courses and Teachers' Specializations - Mercado, Rissa L. (International Journal of Membrane Science and Technology, 2023)
The implementation of the K to 12 programs in the Philippines has significantly expanded vocational education opportunities for students, aiming to enhance their future prospects. However, the issue of teacher-subject mismatch, particularly in TVL (Technical-Vocational-Livelihood) courses, has emerged as a significant challenge affecting teachers, students, implementers, and other stakeholders. This research investigates the prevalence of teacher-subject mismatch in Senior High Schools offering TVL subjects in Agusan del Sur, Philippines. Utilizing qualitative data collection and thematic analysis, four key themes were identified: Qualifications of TVL Teachers, Existence of Teacher-Subject Mismatch, Impact of Teacher-Subject Mismatch, and Policy Enhancement for Teacher-Subject Alignment. Despite possessing qualifications, TVL teachers perceive a concerning presence of teacher-subject mismatch in their schools. Based on the respondents' perspectives analyzed in this study, policy improvements are recommended to address the issue of teacher-subject mismatch in vocational education.